ANALYSIS OF PASSENGER TERMINAL AREA AT PATTIMURA INTERNATIONAL AIRPORT AMBON - Eric Michael Ronteltap; Luky Surachman (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2023)
Pattimura International Airport in Ambon is located at Jl. Dr. Leimena, Laha, Tlk. Ambon District, Ambon City, Maluku 97236. In this study, the researchers used passenger movement data from Pattimura International Airport spanning for the years 2018 to 2022. Prior to 2018, the airport was undergoing a revitalization process. Given both these revitalization efforts and the impact of the Covid-19 pandemic, it has become imperative to conduct an analysis of the terminal's ability to manage the evolving patterns of passenger arrivals and departures. This requires an assessment of the landside aspect to determine the terminal's maximum capacity and to predict when it will reach that capacity. To measure the degree of saturation, the researchers used calculations based on the Standard Busiest Rate method, using the 40th peak hour in accordance with Federal Aviation Administration (FAA) standards. Keywords : Pattimura International Airport Ambon, ; 40th Peak ; FAA method;Peak Hour.